6(6x-8)=96

Simple and best practice solution for 6(6x-8)=96 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(6x-8)=96 equation:



6(6x-8)=96
We move all terms to the left:
6(6x-8)-(96)=0
We multiply parentheses
36x-48-96=0
We add all the numbers together, and all the variables
36x-144=0
We move all terms containing x to the left, all other terms to the right
36x=144
x=144/36
x=4

See similar equations:

| 3x+47=x+18 | | 14x+14/3-13x=14/15 | | n×2=16 | | 14n=90 | | (x+2)/(x+10)=2/7 | | 180=-16x+13+-20x+23 | | (4x)(7x)=448 | | 117=-10x+65+6x+44 | | 3(k+9)+-7=2 | | 3(k-20)=-18 | | 10g−7=93 | | 21x-2=6 | | 3a-4=6a-8 | | 8=2(h+1) | | 8x-16=6x+2 | | Y=-6x^2-24 | | (2+3x)(4-x)=3x(3-x) | | 2=n-6/2 | | 13x-20x=1/3 | | 8g=8+10g | | 2y^2-7=0 | | -1-7f=5-9f | | 7-6s=-5-6s | | 3k+6=4k | | 12z=10z+20-12 | | 12x-7x=2x+5 | | 7=7+1/10t | | -6x+6(2x+-3)=-5-7x | | 0.2/b=20 | | -4m+3m=3/2 | | x^2+(x–4)^2=20^2 | | 3y^2-11y+12=0 |

Equations solver categories